Use of iron sucrose injection in anemia patients with reduced serum iron concentration during hospitalizations of digestive and liver diseases - Hong, Cen; Xu, Xiangbo; Feng, Ruirui; Romeiro, Fernando Gomes [UNESP]; Zhang, Dan; Bai, Zhaohui; Guo, Xiaozhong; Qi, Xingshun (AME Publishing Company, 2021)
Background: Anemia is one of the most common disorders in the world. Serum iron is an essential element for the synthesis of hemoglobin and contribution of the oxygen-carrying ability of red blood cells (RBCs). Iron sucrose injection may effectively correct iron deficiency, increase iron storage, and then improve anemia. The aim of the present study was to evaluate the therapeutic effect of iron sucrose injection in anemia patients with reduced serum iron concentration. Methods: Overall, 95 anemia patients with digestive and/or liver diseases were included. They were divided according to the infusion of iron sucrose injection during hospitalization. The paired sample t test was used for comparison between last and baseline hemoglobin concentration. The independent sample t test was used for comparison of a dynamic change of hemoglobin concentration between patients who received and did not receive infusion of iron sucrose injection. Results: Iron sucrose injection was infused in 74 (77.90%) patients. Mean hemoglobin concentration after infusion of iron sucrose injection was significantly increased (91.61 vs. 94.98 g/L, P=0.011). Δ Hemoglobin concentration was significantly different between patients who received and did not receive infusion of iron sucrose injection (P=0.007). Mean hemoglobin concentration after infusion of iron sucrose injection remained significantly increased in subgroup analyses of patients with cirrhosis (88.30 vs. 91.98 g/L, P=0.035) and gastrointestinal bleeding (85.70 vs. 92.63 g/L, P<0.01). Conclusions: Iron sucrose injection can significantly increase the hemoglobin concentration in anemia patients with serum iron concentration below the lower limit of the normal range.
Keywords: Gastrointestinal bleeding; Hemoglobin; Iron; Iron sucrose injection; Liver cirrhosis